Solar Energy Potential in Horn of Africa: A_x000D_ Comparative Study Using Matlab/Simulink - (:unkn) unknown (My University, 2021)
Geographically, the Horn of Africa is one of the_x000D_ regions that the Equator passes over, providing the opportunity_x000D_ for vigorous solar energy. However, despite the enormous solar_x000D_ energy resources, more than half of the region, 132 million_x000D_ populations have not yet access to electricity. This study presents_x000D_ an overview of the potential of solar energy in the region. Then_x000D_ review the current solar energy status and policies related to it. A_x000D_ Matlab/Simulink model is developed to show the comparative_x000D_ analyses of the solar radiation graphically on the photovoltaic_x000D_ modules and electricity outputs for the Horn of African countries'_x000D_ capitals. As a result of the simulation model, Ethiopia-Addis_x000D_ Ababa receives the highest annual solar radiation of 2915.03_x000D_ kWh/m2_x000D_ -year while Eritrea-Asmara with the lowest annual solar_x000D_ radiation of 2198.47 kWh/m2_x000D_ -year. The annual electrical output of_x000D_ the photovoltaic modules in Ethiopia-Addis Ababa is the highest_x000D_ with 286.685 kWh/year and Eritrea-Asmara 216.214 kWh/year as_x000D_ the lowest in the region. The number of photovoltaic modules and_x000D_ the optimum tilt angles are calculated. For Ethiopia-Addis Ababa,_x000D_ the lowest photovoltaic module number is 10, and the optimum PV_x000D_ tilt angle is 11.163°. For Eritrea-Asmara, the highest photovoltaic_x000D_ module number is 14, with a tilt angle of 15.397°.